Characteristic of Hermetia illucens Fatty Acid and that of the Fatty Acid Methyl Ester Synthesize Based on Upcycling of Perishable Waste - Leong, S.Y. (Springer Science and Business Media B.V., 2020)
Abstract: Physicochemical properties of biodiesel are influenced by the characteristic of fatty acids including chain length, degree of unsaturation and composition of fatty acid. The aim of this work was to investigate the influence of Hermetia illucens fatty acid properties on biodiesel quality using a transesterification reaction. H. illucens larvae were grown on fruit waste and food waste. The harvested pre-pupae were processed into dry biomass and stored in a container for further use. H. illucens pre-pupae were transesterified with methanol in the presence of sulphuric acid as catalyst. The reaction was conducted using methanol to sample mass of 6:1, reaction time (255Â min), reaction temperature (50Â Â°C), and catalyst loading (20v/v). Biodiesel quality was tested according to the ASTM and EN standard. The degree of unsaturation, long chain saturated factor and methyl ester composition of each biodiesel also influence the biofuelâs properties. Fatty acid extracted from the H. illucens biomass showed high saturated fatty acid (SFA) derived from both feeds. Lauric acids were found to be the predominant SFA. The properties of FAME produced under optimum conditions, including density, kinetic viscosity, copper strip corrosion, oxidation stability and cloud points were in accordance with EN 14214 and ASTM 6751 biodiesel standards. Graphic Abstract: Figure not available: see fulltext.. Â© 2020, Springer Nature B.V.